Economics of legume-wheat (Triticum aestivum) cropping systems under different levels of irrigation
A field experiment was conducted from 1988-89 to 1992-93 to evaluate the productionpotential and economic returns in wheat (Triticum aestivum L. emend. Fiori & Paol.